(3EYQGH GdLed hCTHGg GdLed (B/s - (3bHGhI, aNQ GdOjf,s 1933- ((3GdbGgQI, eUQ (B:s (3OGQ GdSdGe ddWHGYI hGdfTQ hGdJhRjY hGdJQLeIs, 2024)
(3jfbSe gPG GdcJGH Edi CQHYI aUhd(B: (3GdaUd GdChd, hgh dCbSGe GdLed, HOCJg HGdaQb Hjf GdLedI hGdcdGe(B. (3Ke YQVJ dCbSGe GdLed, eHjfG VQhQI GdGgJeGe HGdLedI GdTQWjI, hEZaGd GdLedI GdXQajI(B. (3Ke hbaJ YfO GdLedJjf (B: (3GdcHQi hGdUZQi, dCaUd CfhGY cdG efgeG, eSJYjfG HeG JMbb ef CbSGe GdLed, hGdaUd GdKGfj, hgh ddLed GdJj dG eMd dgG, GSJgddJg HHjGf YdGbI GdLed HGdEYQGH, Ke aUdJ GdHMK aj GdLed GdYTQ (B: (3GdGHJOGFjI, GdGSJFfGajI, LedI GdTQW ZjQ GdXQaj, GdGYJQGVjI, GdJaSjQjI, LhGH GdbSe, LhGH GdTQW ZjQ GdLGRe, LhGH GdTQW GdLGRe ZjQ GdebJQf HGdaGA Ch EPG, UdI GdehUhd, GdJGHYI dLedI dG eMd dgG, hGdaUd GdKGdK, hgh ddLed GdJj dgG eMd, egOJ dg HHjGf GdeMd GdEYQGHj ddLedI, hJhVjM GdeaQO GdPj JDhd Hg GdLedI, cGdeUOQ GdeDhd Ohf MQa eUOQj, hGdeTJb, hGdaYd GdeVGQY(B. (3Ke YQVJ ddLed GdYTQ (B: (3GdhGbYI eHJOC, GdhGbYI NHQG, GdhGbYI aGYdG, GdhGbYI eaYhdG Hg, GdhGbYI MGdG, GdhGbYI eSJKfi, GdhGbYI eVGaG Edjg, GdhGbYI LhGHG dTQW LGRe ebJQfI HGdaGA Ch EPG, GdJGHYI deaQO, GdJGHYI dLedI dgG eMd (B... (3EdN(B.s
Keywords: (3GddZI GdYQHjIs -- (3fMhs